2006
DOI: 10.1300/j027v25n01_05
|View full text |Cite
|
Sign up to set email alerts
|

Translating Evidence-Based Physical Activity Interventions for Frail Elders

Abstract: The population shift to an older America has initiated a great deal of interest in the impact of evidence-based physical activity interventions on older adults. Physical activity for older adults has tremendous benefits and is recognized as one of the most powerful health interventions for improving seniors' ability to function and remain independent in the face of active health problems and yet the majority of all older adults remain largely sedentary. To date, few programs have been developed that apply thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…This reduction in depression may be attributed to several aspects of the intervention. Physical activity, in addition to producing reductions in BMI, has been found to reduce levels of depression among older adults (Strawbridge et al, 2002; Wieckowski & Simmons, 2006; Yan, Wilber, Aguirre, & Trejo, 2009). In addition, the group program promoted social interaction, another factor associated with reduced depression (Strawbridge et al, 2002; Wieckowski & Simmons, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This reduction in depression may be attributed to several aspects of the intervention. Physical activity, in addition to producing reductions in BMI, has been found to reduce levels of depression among older adults (Strawbridge et al, 2002; Wieckowski & Simmons, 2006; Yan, Wilber, Aguirre, & Trejo, 2009). In addition, the group program promoted social interaction, another factor associated with reduced depression (Strawbridge et al, 2002; Wieckowski & Simmons, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity, in addition to producing reductions in BMI, has been found to reduce levels of depression among older adults (Strawbridge et al, 2002; Wieckowski & Simmons, 2006; Yan, Wilber, Aguirre, & Trejo, 2009). In addition, the group program promoted social interaction, another factor associated with reduced depression (Strawbridge et al, 2002; Wieckowski & Simmons, 2006). Anecdotal evidence from participants suggested that participants teamed up with one another to exercise on their own, independent of the Be Well classes, with several participants noting a newly established commitment to their health goals and Be Well attendance arising from new friendships developed in classes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Tapping these potential benefits will require adaptation to local conditions, measurement of outcomes and costs, and experimentation with financial incentives and business models. Established normative values for physical performance in the elderly 20,21 and the success of home-based exercise interventions for the frail elderly in the United States 22,23 provide additional support to the feasibility of community-based exercise interventions for stroke patients. The absence of serious adverse events and the widespread community support for APA in Italy suggest that the gains in quality of life for stroke patients will be well worth the effort of implementation.…”
Section: Translation?mentioning
confidence: 99%